VD_FINDINFO Décision / 2022 / 248 vom 4. April 2022 - VD Tribunal cantonal (2022)
REJET DE LA DEMANDE, RISQUE DE RÉCIDIVE, MESURE DE SUBSTITUTION À LA DÉTENTION | 221 al. 1 let. c CPP (CH), 230 CPP (CH), 237 CPP (CH)